Beauty ranking of mammalian species kept in the Prague Zoo: does beauty of animals increase the respondents' willingness to protect them? - Landová, Eva; Poláková, Petra; Rádlová, Silvie; Janovcová, Markéta; Bobek, Miroslav; Frynta, Daniel (Die Naturwissenschaften, 2018)
Aesthetic preferences for animals correspond with the species' presence in the worldwide zoos and influence the conservation priorities. Here, we investigated the relationship between the willingness of respondents to protect mammals and some attributed characteristics such as their aesthetic beauty. Further, several methodological aspects of measuring mammalian beauty were assessed. Animal beauty was associated not only with the respondents' willingness to protect the species but also with its attributed dangerousness and usefulness. We found that the most preferred animals were carnivores and ungulates, whilst smaller species of rodents and afrosoricids were unpopular. The main characteristics determining that an animal will be ranked as beautiful were complex fur pattern and body shape. We demonstrated that the position of mammalian species along the 'beauty' axis is surprisingly stable, no matter the form (illustrations vs photographs), context of stimulus presentation (several number of stimuli per family vs one randomly selected species per family), or the method of beauty evaluation (relative order vs Likert's scale).
Keywords: Esthetics; Czech Republic; Beauty; Zoo; Animals, Zoo; zvířata v ZOO; zvířata; Česká republika; estetika; Mammals; krása; savci; Animals; Conservation of Natural Resources; Animal conservation; zachování přírodních zdrojů; Preferences; Human perception